Novel pleiotropic risk loci for melanoma and nevus density implicate multiple biological pathways - David L. Duffy (Nature Portfolio, 2018)
Melanocytic nevus count is associated with melanoma risk. In this study, a meta-analysis of 11 nevus GWAS studies identifies novel SNPs in KITLG and 9q32, and bivariate analysis with melanoma GWAS meta-analysis reveals that most nevus genes affect melanoma risk, while melanoma risk loci do not alter the nevus count.